The Digital Divide Revisited: Connectivity, Devices, and the Hidden Barriers to Global EdTech Equity - Amiri, Sayed Mahbub Hasan (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2025)
This article interrogates the persistent inequities in global educational technology (EdTech) deployment, arguing that traditional “access gap” frameworks fail to address the complex architecture of digital exclusion. Through mixed-methods desk research analyzing 140+ scholarly works, institutional reports, and case studies across 15 countries, we identify five interdependent hidden barriers undermining EdTech equity: (1) the affordability mirage of hidden data/repair costs, (2) digital literacy deserts among teachers/students, (3) infrastructure fragility (electricity/ connectivity), (4) cultural-linguistic irrelevance, and (5) policy-governance gaps. Empirically grounded in contexts from Rwanda’s One Laptop Per Child program to India’s DIKSHA platform, findings reveal how these barriers disproportionately exclude marginalized learners, particularly in low-income and remote communities. The study advances a transformative solution framework centered on zero-cost connectivity architectures, situated teacher capacity building, adaptive hybrid infrastructure, decolonized content co-creation, and agile multistakeholder governance. We contend that only by addressing these systemic, human, and socio-technical dimensions can EdTech fulfil its promise as an educational equalizer. Urgent implementation of these evidence-based strategies could prevent an estimated $17 trillion in lost GDP by 2040 while reclaiming the democratic potential of digital learning.